Multiple true or false questions in haematology & pathology for health sciences undergraduates - Muhammad, Siti Aesah @ Naznin (IIUM Press, 2014)
This book is to guide health sciences undergraduates students in particular preclinical medical students in assessing their knowledge in haematology and pathology. The unique feature of this book is that the answers to the questions are not provided in order to encourage students to search for the answers themselves. This will foster and enhance learning in haematology and pathology at individual level and as a group.